(untitled) (Global Journal of Management and Business Research, 2024)
This study investigates the concept of quality of work life QWL a term that holds various interpretations and represents the complexity of working conditions and their impact on employee well-being The research adopts a documentary methodology allowing for a comprehensive analysis of primary and secondary sources such as academic articles research reports and relevant case studies It examines progress in the field of QWL its practical applications in businesses and the challenges that organisations in developing countries face when attempting to implement these practices The article presents a theoretical framework that contextualises the emergence of the QWL concept highlighting the influence of human resource management practices on the appreciation and well-being of workers